Scholastic year in sports 2020 - Buckley, James, Jr., 1963- (Scholastic Inc., 2019)
Presents a wide-ranging review of sports stories and statistics from 2019, from the U.S. Women's Soccer World Cup Championship to the first-ever NBA championship win by a team outside the United States, the Toronto Raptors, as well as stories of lesser-known sports and superstars.